The Causal Relationship Model of Quality Control Standard Factors Affecting Success of Accounting Offices in Thailand - Thipwiwatpotjana, Suthira (Humanities, Arts and Social Sciences Studies, 2019)
This study was to test the causal relationship model of quality control standard factors affecting the success of accounting offices. The population in this study was 129 accounting offices in Thailand that are certified by Department of Business Development. The informants were managers or head officers. Data were collected using questionnaires. The data were analyzed using descriptive statistics and a structural equation modeling (SEM). The fit indices showed that the proposed model had a good fit (χ2 = 42.765, df = 31, p = 0.078, χ2/df = 1.380, GFI = 0.941, and RMSEA = 0.057). Document management and resource management had direct effects on the success of accounting office, with significant path coefficients of 0.66 and 0.26, respectively. Executive responsibility, ethical requirement, process related to customer, monitoring, and work practice had indirect effects on the success of accounting office, with significant path coefficients of 0.58, 0.27, 0.20, 0.50, and 0.23, respectively.